2022
DOI: 10.1111/ene.15471
|View full text |Cite
|
Sign up to set email alerts
|

Effects of blood lipids and lipid‐modifying drugs on intracranial aneurysms

Abstract: Background and purpose:We used two-sample Mendelian randomization (MR) to examine the effects of blood lipids and lipid-modifying drugs on intracranial aneurysm (IA). Methods: Genetic variants for the effects of high-density lipoprotein cholesterol (HDL-C), apolipoprotein A1, low-density lipoprotein cholesterol (LDL-C), apolipoprotein B, and triglycerides and targets for lipid-modifying drugs were selected from the genome-wide discovery analyses of the UK Biobank. Summary-level data on IAs were obtained from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Nevertheless, additional research is warranted to elucidate the mechanistic involvement of ApoE in the pathogenesis of arterial aneurysms. According to reports, a negative correlation was observed between HDL and IA as well as ruptured IA [ 25 ]. Additionally, our study revealed a positive correlation between HDL and mean methylation in both males and females.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, additional research is warranted to elucidate the mechanistic involvement of ApoE in the pathogenesis of arterial aneurysms. According to reports, a negative correlation was observed between HDL and IA as well as ruptured IA [ 25 ]. Additionally, our study revealed a positive correlation between HDL and mean methylation in both males and females.…”
Section: Discussionmentioning
confidence: 99%
“…2023), with TNF-α being one of the key factors in aneurysm formation and growth [ 50 - 52 ]. High-density lipoprotein cholesterol (HDL-C) and low-density lipoprotein cholesterol (LDL-C) were found to reduce the risk of IA and IA rupture [ 53 ].…”
Section: Biomarkers Of Aneurysm Development and Rupturementioning
confidence: 99%
“…Moreover, the presence of interleukins was found to be associated with IA development risk and instability (Monsour et al 2022, Liu et al 2023, with TNFα being one of the key factors in aneurysm formation and growth [5052]. Highdensity lipoprotein cholesterol (HDLC) and lowdensity lipoprotein cholesterol (LDLC) were found to reduce the risk of IA and IA rupture [53].…”
Section: Biomarkers Of Aneurysm Development and Rupturementioning
confidence: 99%
“…Statins and antiplatelet agents are commonly used for prevention of stroke in patients with hyperlipidemia and those with a previous ischemic stroke. Several recent studies have emphasized the potential protective effect of these agents for aneurysmal rupture (51)(52)(53)(54)(55)(56). Potential mechanisms include anti-inflammatory effects, stimulation of extracellular matrix production, and chemotactic migration of mesenchymal progenitor cells to stabilize aneurysm walls (57,58).…”
mentioning
confidence: 99%